Implikasi Teori Belajar Behavioristik Edwin Ray Guthrie Dalam Menangani Malas Belajar Siswa - Syahrani, Juwita; Putri, Adinda Salsameywa; Khairunnisa, Khairunnisa; Pulungan, Alimatuk Sakdiyah; Abdillah, Risyad Fikri; damayanti, Neffi Damayanti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this discussion is to solve the problems experienced by students who are lazy to learn through a behavioristic learning theory approach. This approach is one of the methods for dealing with educational problems, especially student learning. In creating a learning atmosphere and several aspects of learning support, especially the lack of student motivation to learn, causing a feeling of laziness. This behavioristic theory in relation to students, educators do have an important role in the learning and learning process. This study uses a literature study approach and uses literature (library) after identifying the data obtained, then concluding about the problem being studied. Then do the existing data analysis. The analysis used is descriptive qualitative research. As well as in the behavioristic theory approach emphasizing a process of changing behavior and the consequences of interactions between stimulus and response, this is important to apply to students in the learning process and learning for education. Keywords: Lazy to learn, Behavioristic Theory.